Otoritas Baitul Mal Aceh Dalam Menyukseskan Sustainable Development Goals - Rahmat Kurniawan (Madania: Jurnal Ilmu-Ilmu Keislaman, 2022)
SDGs as a national development agenda opens opportunities to involve various elements in the success of its 17 goals. Baitul Mal Aceh as an institution that manages religious assets in their distribution can take a role towards these goals based on the authority they have. This study examines the efforts made by Baitul Mal Aceh based on the authority it has in distributing Islamic philanthropic assets and their relevance in the success of the SDGs agenda. This research focuses on Aceh Province. Data collection is done through observation and documentation. The analysis of the data that has been collected is done in depth. The results of the study show that the programs run by Baitul Mal using managed religious assets have some of the same targets as detailed in the SDGs. The authority possessed by Baitul Mal Aceh has been perfected in Aceh Qanun Number 3 of 2021. Funds for the Muslim community in Baitul Mal Aceh are distributed in various forms, such as consumptive and productive distribution. Consumptive assistance such as the provision of basic necessities or food is given as a short-term response to the difficulties experienced by mustahik, while productive assistance such as the provision of capital and training is considered a long-term response because the aim is to build and increase independence so as to obtain sustainable prosperity. With the distribution of philanthropic funds, it can finally help alleviate poverty and provide welfare as offered by the SDGs in national development efforts.